2014
DOI: 10.1088/0004-637x/795/1/11
|View full text |Cite
|
Sign up to set email alerts
|

Latitude Survey Investigation of Galactic Cosmic Ray Solar Modulation During 1994-2007

Abstract: The Galactic cosmic ray spectrum exhibits subtle variations over the 22 yr solar magnetic cycle in addition to the more dramatic variations over the 11 yr sunspot cycle. Neutron monitors are large ground-based detectors that provide accurate measurements of variations in the cosmic ray flux at the top of the atmosphere above the detector. At any given location the magnetic field of the Earth excludes particles below a well-defined rigidity (momentum per unit charge) known as the cutoff rigidity, which can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
100
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(109 citation statements)
references
References 35 publications
8
100
1
Order By: Relevance
“…Note that the period of high tilt angle during the previous solar cycle (during 2000) was much shorter than during the present solar cycle (during 2010-2014). We also confirm the results of [19,21] that the slope of the linear relationship between NMs at different cutoffs was higher during the time of negative solar magnetic polarity (Figure 3(b)). This Figure also shows that the slopes were very similar during the periods of rising and falling GCR flux at Doi Inthanon during the qA < 0 period.…”
Section: Pos(icrc2017)036supporting
confidence: 90%
See 3 more Smart Citations
“…Note that the period of high tilt angle during the previous solar cycle (during 2000) was much shorter than during the present solar cycle (during 2010-2014). We also confirm the results of [19,21] that the slope of the linear relationship between NMs at different cutoffs was higher during the time of negative solar magnetic polarity (Figure 3(b)). This Figure also shows that the slopes were very similar during the periods of rising and falling GCR flux at Doi Inthanon during the qA < 0 period.…”
Section: Pos(icrc2017)036supporting
confidence: 90%
“…Note that these time periods correspond to relatively lower tilt angles, roughly speaking when the tilt angle was below about 50 • . Such a linear relationship was also found for a ship-borne NM and the McMurdo NM during 1994-2007 [19], with the exception of the year 2000, which again was when the tilt angle was high. Note that the period of high tilt angle during the previous solar cycle (during 2000) was much shorter than during the present solar cycle (during 2010-2014).…”
Section: Pos(icrc2017)036supporting
confidence: 63%
See 2 more Smart Citations
“…For example, from comparing the HCS tilt angles with the NM counts of one ground-based station (Newark), Cliver, Richardson, and Ling (2013) first suggested (already in 2011) that the drift of charged GCR was not a dominant factor in the minimum of cycle 24, contrary to expectations. Recent studies found an association between the 2009 anomalous peak and higher values of the diffusion coefficient (e.g., Alania, Modzelewska, and Wawrzynczak, 2014;Nuntiyakul et al, 2014). Other studies also found evidence of the remission of the drift process in the solar modulation during the last minimum and suggested that changes in the solar wind turbulence might produce a diffusion-dominated solar modulation period (e.g., Starodubtsev and Grigoryev, 2011;Potgieter et al, 2014).…”
mentioning
confidence: 97%